Optical Behavior of an Enhanced Monofocal Intraocular Lens Compared with a Standard One - María García-Montero; Nuria Garzón; Veronica Gonzalez-Fernandez; José Antonio Gómez-Pedrero; César Albarrán-Diego (Applied Sciences, 2023)
The aim of this work was to compare an enhanced monofocal (RayOne EMV RAO200E, Rayner) and standard monofocal (RayOne RAO600C Aspheric, Rayner) intraocular lenses (IOLs) for three nominal powers (+10.00 D, +20.00 D and +30.00 D) as a function of the optical aperture diameter (pupil diameter) using a commercial Schlieren phase-shifting deflectometer NIMO TR1504 (Lambda-X, Belgium). From the wavefront maps measured by this instrument, the radial power profiles, the spherical aberration coefficients of the Zernike polynomial expansion (as a function of the optical aperture radius), and the root-mean-square (RMS) of the high-order aberrations (HOAs) were obtained and analyzed by comparing the two models. The results showed that the effective added power that could be obtained with the enhanced model depended directly on the pupil size and the power of the IOL implanted. The higher additions were achieved with the higher nominal IOL powers. The relationship between the pupil diameter, the corneal aberration of the patients and the power profile of these IOLs could have a crucial implication on the far distance and the final effective addition. However, it is important to note that these findings should be clinically validated through the implantation of these models in patients’ lenses.